PENGENAAN PPh FINAL DAN BPHTB TERHADAP PERMOHONAN HAK BARU ATAS TANAH DAN/ATAU BANGUNAN YANG BELUM BERSERTIPIKAT YANG DIALIHKAN SETELAH BERSERTIPIKAT DI KOTA BINJAI - YUSNIAMAN HAREFA (PREMISE LAW JURNAL, 2016)
An applicant who requests for a new right of uncertified land and/or building (the first land registration) to the Land Office, Binjai, is required to pay PPh Final PHTB and BPHTB. The levying on PPh Final PHTB is based on UU PPh No. 36/2008 in conjunction with PP No. 71/2008 on the Levying on Income Tax of the Income from the Transfer of Title on Land and/or Building. The levying on BPHTB is based on UU PDRB No. 28/2009 in conjunction with the Regional Regulation of Binjai No. 2/2011 on BPHTB. After the land is certified and transferred, the seller is required to pay for PPh Final PHTB and the buyer is required to pay for BPHTB so the land owner pays for PPh Final PHTB twice and pays for BPHTB once. Logically, it is impossible for the land owner to sell his land twice or more, and thus he has to pay for PPH twice or more. This is the reason why the title of the research is “The Levying on PPh Final PHTB and BPHTB of the applicant who Requests for a New Right on Uncertified Land and/or Building Transferred and after it is certified at Binjai.” Keywords: PPH Final PHTB, BPHTB, Request for New Right (the First Land Registration), Aspect of Justice